2022
DOI: 10.3390/app12115657
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Gas Leakage Model and Research on the Leakage Field Strength Characteristics of R290 in Limited Space

Abstract: Some alternative refrigerants with excellent environmental performance often have different flammable limits. When refrigerant leaks, the external space may have a certain explosion risk if the refrigerant is not diffused timely. To understand the leakage and diffusion characteristics of the refrigerant, an improved gas leakage model was proposed in this paper, and the accuracy verification of the improved model was developed. Based on the above works, taking R290 as the research object, the variation law of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…According to the mathematical model of hole leakage [21][22][23], the characteristics of gas flow, such as mass flow rate (Q) and mean flow velocity in the leak hole, can be divided into sonic flow and subsonic flow according to the critical pressure ratio (CPR)…”
Section: 𝐶𝑃𝑅mentioning
confidence: 99%
See 2 more Smart Citations
“…According to the mathematical model of hole leakage [21][22][23], the characteristics of gas flow, such as mass flow rate (Q) and mean flow velocity in the leak hole, can be divided into sonic flow and subsonic flow according to the critical pressure ratio (CPR)…”
Section: 𝐶𝑃𝑅mentioning
confidence: 99%
“…respectively, where ξ is given by Equation (23). Finally, the displacement fields generated by the gas leakage can be summarized as follows…”
Section: Displacement Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though they provide a valuable reference, these literature studies mainly focused on the thermodynamic characteristics of ORC itself, rather than the thermodynamic coupling principles between the ORC and the air compression process. The energy conversion from waste heat to electricity has been demonstrated to be an efficient way for energy utilization; however, some study results also show that the ORC power generation efficiency is significantly affected by the compression heat grade and its volatility [18], and may suffer from refrigerant leakage [19].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we determined the FRS from the reported date [20]. where 𝑢′𝑣′ is assumed to be the mean value of the product of 𝑣 𝑣 , and According to the mathematical model of hole leakage [21][22][23], the characteristics gas flow, such as mass flow rate (Q) and mean flow velocity in the leak hole, can be vided into sonic flow and subsonic flow according to the critical pressure ratio (CPR)…”
mentioning
confidence: 99%